ANALISIS YURIDIS PERBUATAN DENGAN SENGAJA MEMBERI KESEMPATAN KEPADA KHALAYAK UMUM UNTUK MELAKUKAN PERMAINAN JUDI (ANALISIS PUTUSAN NOMOR:161/PId.B/2022/SRH) - Silaban, Erwin Ade Putra; Sahari, Alpi (JURNAL DOKTRIN REVIEW, 2023)
The government has taken steps and efforts to curb gambling, limiting it to the smallest possible environment, gambling which still frequently occurs in the Legal Area of Serdang Bedagai Regency, such as KIM gambling carried out by Serdang Bedagai residents who have been convicted and found guilty as per Decision Number: 161 /Pid.B/2022/Srh. The formulation of the problem is how the provisions of the criminal act of deliberately giving the general public the opportunity to play gambling games, and how law enforcers attempt to apply criminal sanctions against perpetrators who open gambling businesses, as well as how the judge considers cases of criminal acts of deliberately giving the public an opportunity. It's common to play gambling games. The research method used is normative legal research. In relation to the criminal provisions, the act of intentionally giving the general public the opportunity to play gambling games is regulated in Article 303 of the Criminal Code, and law enforcement efforts in implementing criminal sanctions against perpetrators who open gambling businesses in the case of Decision Number: 161/PId.B/2022/ SRH, the Defendant as the perpetrator who carried out the action deliberately gave the general public the opportunity to play gambling games, and as a form of law enforcement, the defendant's actions are regulated and punishable by crime in Article 303 paragraph (1) 1st of the Criminal Code in conjunction with Article 303 paragraph (1) 2nd of the Criminal Code, as well as the Judge's Considerations in criminal cases involving intentionally giving the general public the opportunity to play gambling games.